Measurement of Ministry/Institution Budget Performance Efficiency Using Data Envelopment Analysis (DEA) - irawan, shiddiq ardhi (Jurnal Anggaran dan Keuangan Negara Indonesia (AKURASI), 2020)
Efficiency is one of the tools used by the Government to measure the success of an activity. Based on PMK Number 214/ PMK.02/2017 it is regulated regarding the measurement and Evaluation of Budget Performance for the implementation of Work Plans and Ministries/Institutions Budgets. To measure budget performance achievement based on aspects of implementation 4 (four) variables i.e. budget absorption, output achievements, efficiency, and consistency of budget absorption towards planning, are used. This study aims to measure the efficiency level of Ministries/Institutions budget performance using Data Envelopment Analysis (DEA). However, the variables used are not only based on measurement aspects of implementation according to PMK Number 214/PMK.02/2017 but also the number of satker (satuan Kerja). The approach used in the DEA model is Constant Return to Scale (CRS) model and Variable Return to Scale (VRS) model. This study uses the DEA model approach by comparing the results of the CRS model with VRS model. Based on DEA results, the number of Ministries/Institutions that have efficient scores is less than the number of Ministries/Institutions with inefficient scores. In addition, based on the value of slacks in each Ministries/Institutions, the variables that need to be improved are the coordination among satkers in when they are recording their performance achievements in the SMART application. Other variables that also require improvements are the ministry/agency’s willingness to revise their Disbursement Plan (RPD) after each budget revision and the speed at which they spend their budget once DIPA is stipulated.